"Designer cytokines" targeting the tumor vasculature—think global and act local. Issue 2 (9th January 2020) - Kammertoens, Thomas; Kemna, Josephine; Leisegang, Matthias
Abstract : Tumor necrosis factor (TNF) was discovered in 1975 as a lipopolysaccharide‐induced serum factor that causes necrosis of tumors (Carswell et al, 1975). It was later found that TNF and cachectin, a factor causing wasting disease, were one and the same molecule (Beutler et al, 1985). Studies on the inflammatory activity of TNF have been translated into clinical success, namely blocking antibodies used to suppress autoimmune diseases. Research on TNF anti‐tumor activity, in contrast, has not yet resulted in a therapeutic breakthrough. This may change, based on a study by Huyghe et al (2020) describing novel "designer cytokines" (TNF and interferon‐γ) that increase local activity by targeting the CD13‐positive tumor vasculature, while simultaneously lowering the binding affinity to the respective cytokine receptor, thereby reducing off‐target effects on normal cells. Abstract : Despite TNF anti‐tumor activity, its therapeutic use has been limited by high toxicity. T. Kammertoens and colleagues discuss the work from Huygue et al, in this issue of EMBO Molecular Medicine, which describes new cytokines engineered to overcome these limitations.